Home medicine : the Newfoundland experience - Crellin, J. K. (McGill-Queen's/Hannah Institute studies in the history of medicine, health, and society, 1994)
Based on material from the Folklore Archives at Memorial University as well as other sources, Crellin's catalogue includes such topics as abortion, baldness and hair preparations, blood-letting, cancer, drunkenness, female complaints, Gin Pills, herbs, midwifery and childbirth, Newfoundland stomach, poultices, prepared cures, rheumatism and arthritis, and tonics. Looking at the interplay between mainstream physicians and alternative treatments, and the effect of folk beliefs on today's self-care practices, Crellin examines how the advent of modern medicine has affected self-treatment. His extensive use of oral and written commentary gives the book a personal dimension that adds to its charm. Home Medicine will appeal to those interested in alternative medicine, folklore, and Atlantic Canada, and to medical and social historians.